Wealth Impact of Unit Rights Offerings to Debt Holders: Evidence from Australia - Siti Nurhidayah Mohd Roslen; Cheng Fan Fah; Norhuda Abdul Rahim (Australasian Accounting, Business and Finance Journal, 2023)
We examine the debt holders' wealth effect of Australian firms and the factors that determine firms' decision to issue unit rights. The sample consists of 638 offerings observations spanning from year 2000 to 2014. Probability of default has been used as the proxy for debt holders wealth. We also use probit model to gauge determinants of firms' choice in issuing unit rights. As the robustness test, logit model was also presented. Aligned with Sequential Financing Hypothesis by Schultz (1993) and Signaling Hypothesis as in Chemmanur and Fulghieri (1997), we find that firms with small size, low issuance proceeds, high risk, low managerial ownership and positive growth prospect tend to issue unit rights. We also obtain findings that support to Leverage Risk Reduction Hypothesis which suggest that debt holders' return is favorably affected by lower financial leverage.
Keywords: Unit rights; Debt holders’ wealth; Probability of default; Equity warrants; Australian Stock Exchange